Research on the Transformation Area Deformation of Topographic Map Under the Background of "Multi Conformity". Issue 1 (February 2021) - Yong, Lei; Lihui, Wang; Zhu, Chen; Chuanjian, Ren; Zhihong, Wang
Abstract: The urban independent coordinate system based on CGCS2000 has a relatively strict conversion correspondence with CGCS2000 coordinate system. Based on the surveying and mapping technical force of class a unit, the conversion of control points can be realized and high precision can be achieved. In the process of topographic map transformation, due to the influence of side length projection deformation, it will have an impact on the area of engineering construction plot. Through the coordinate conversion function of the digital mapping software, the topographic map is transformed to explore the change rate of the converted area and provide decision-making basis for the planning and construction departments.